2017
DOI: 10.1080/21645515.2017.1387345
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a novel seasonal influenza preservative-free vaccine manufactured in Kazakhstan: Results of a randomized, comparative, phase II clinical trial in adults

Abstract: Comparison of the allantoic inactivated split vaccine obtained in vaccines RIBSP and VAXIGRIP®, showed similar immunogenic activity. Both vaccines were safe for the study participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…14,15 RIBSP vaccine was also safe and immunogenic in phase II clinical trials in healthy subjects under 60 compared to the VAXIGRIP® vaccine (widely used for vaccination of the risk groups in the Republic of Kazakhstan). 16 The humoral immune response to RIBSP vaccine meets all three requirements of the European Committee for Medical Products for Human Use of the European Medicines Agency (CHMP) CPMP/ BWP/214/96 and showed similar profile with VAXIGRIP®. 17 Evaluation of the immunogenic activity of RIBSP vaccine showed that the highest seroconversion rate for А/ H1N1pdm09 component reached 87.0% 21 days after vaccination, i.e.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…14,15 RIBSP vaccine was also safe and immunogenic in phase II clinical trials in healthy subjects under 60 compared to the VAXIGRIP® vaccine (widely used for vaccination of the risk groups in the Republic of Kazakhstan). 16 The humoral immune response to RIBSP vaccine meets all three requirements of the European Committee for Medical Products for Human Use of the European Medicines Agency (CHMP) CPMP/ BWP/214/96 and showed similar profile with VAXIGRIP®. 17 Evaluation of the immunogenic activity of RIBSP vaccine showed that the highest seroconversion rate for А/ H1N1pdm09 component reached 87.0% 21 days after vaccination, i.e.…”
Section: Introductionmentioning
confidence: 79%
“…The seroconversion rates for А/ H3N2 and B also exceeded the same rates of VAXIGRIP®. 16 The obtained results demonstrated that RIBSP vaccine provided seroconversion rates for all influenza vaccine components significantly exceeding CPMP/EWP/214/96 criteria for adults.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…12 Sesay et al reported results from a randomized multicenter phase III trial assessing the lot-to-lot consistency of the 2014-5 Northern Hemisphere quadrivalent split-virion inactivated influenza vaccine, showing that its immunogenicity was superior for the added B strain and safety was similar with that of trivalent inactivated influenza vaccine in younger and older adults. 13 Moreover, Sarsenvayeva et al showed that RIBSP 88 and VAXIGRIP have similar immunogenic and safety profiles, 14 whereas Long et al reported that the wild-type A/Solomon Islands/3/2006 (H1N1) (SI/06wt) could be used for large-scale vaccine production with sufficient safety and efficacy, as confirmed by animal experiments with mice and ferrets. 15…”
Section: Vaccinesmentioning
confidence: 99%